One Spore more - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Innocent Messo Loukelo works for the Association for Agricultural and Rural Development (ADAR) in Nkayi, Republic of Congo. He has a very interesting idea for the future of Spore. 'I'd like to see a bi-monthly magazine similar to Spore, but in which...